Amina Wadud's Gender Hermeneutics on QS. An-Nisa: 34: Criticism of Patriarchal Bias and Its Relevance to Contemporary Women's Thought - Cahya, Hafiza Afari; Bukhari, Rauuf; Yumna, Hayatul; Milhan, Rumaisha; Akbar, Abil; Nurrohim, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines Amina Wawud's interpretation of QS. An-Nisa: 34 through a feminist interpretive approach in response to gender bias in classical interpretations that tend to be patriarchal. The focus of this study is how the dominance of traditional interpretations gives legitimacy to the superiority of men over women in the domestic realm. The purpose of this research is to explore the hermeneutic offer of Wadud that is more oriented towards gender justice and equality. The research uses a qualitative method based on literature studies with primary sources in the form of Amina Wadud's work Qur'an and Woman. The results of the study show that Wadud interprets the word qanitāt as